Italian Consensus Conference on Guidelines for preoperative treatment in acetabular fractures - Aprato, Alessandro; Nardi, Michele; Arduini, Mario; Bove, Federico; Branca Vergano, Luigi; Capitani, Dario; Casiraghi, Alessandro; Cavanna, Matteo; Cominetti, Gabriele; Commessatti, Matteo; Favuto, Marco; Ferreli, Alberto; et al. (Acta Biomedica Atenei Parmensis, 2021)
Preoperative management of acetabular fracture is a major problem and no consensus has been reached in literature on the optimal treatment of this problem. We present the results of the First Italian Consensus Conference on Acetabular fracture. An extensive review of the literature has been undertaken by the organizing committee and forwarded to the panel. Members were appointed by surgical experience with acetabular fractures. From November 2017 to January 2018, the organizing committee undertook the critical revision and prepared the presentation to the Panel on the day of the Conference. Then 11 recommendations were presented according to the 11 submitted questions. The Panel voted the recommendations after discussion and amendments with the audience. Later on, a second debate took place in September 2018 to reach a unanimous consent. We present results of the following questions: does hip dislocation require reduction? Should hip reduction be performed as soon as possible? In case of unsuccessful reduction of the dislocation after attempts in the emergency department, how should it be treated? If there is any tendency toward renewed dislocation, how should it be treated? Should Computed Tomography (CT) scan be performed before reduction? Should traction be used? How can we treat the pain? Is preoperative ultrasound exam to rule out vein thrombosis always necessary? Is tranexamic acid intravenous (IV) preoperatively recommended? Which antibiotic prophylactic protocols should be used? Is any preoperative heterotopic ossification prophylaxis suggested?In this article we present the indications of the First Italian Consensus Conference: a hip dislocation should be reduced as soon as possible. If unsuccessful, surgeon may repeat the attempts optimizing the technique. Preoperative CT scan is not mandatory before reduction. Skeletal traction is not indicated in most of the acetabular fracture. Standard pain and antibiotic prophylactic protocols for trauma patient should be used. Preoperative ultrasound exam is not recommended in all acetabular fracture. Tranexamic acid should be preoperatively used. There is no indication for preoperative heterotopic ossification.